Re‐evaluation of butane (E 943a), isobutane (E 943b) and propane (E 944) as food additives - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Bastos; Polly Boon; Biagio Fallico; Reginald Fitzgerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal)
Abstract The Panel on Food Additives and Flavourings (FAF) provides a scientific opinion re‐evaluating the safety of butane (E 943a), isobutane (E 943b) and propane (E 944) as food additives. Butane, isobutane and propane are short‐chain (C3–C4) alkanes, which are in gaseous state at room temperature. Their currently permitted use in food is in vegetable oil pan spray (for professional use only) and water‐based emulsion spray as propellants at quantum satis. They can also be used in food colour preparations with a maximum residual limit of 1 mg/kg in food. Two interested business operators (IBOs) provided information in response to the call for data published by EFSA reporting typical and maximum use levels. The toxicological hazards of the three gases via inhalation are known, however this route of exposure is not considered relevant for their safety assessment as food additives. Existing EU specifications for the three food additives already contain limits for the toxic impurity 1,3‐butadiene (1,3‐BD), however due to a lack of information on the manufacturing processes used, uncertainties do remain regarding the potential presence of other impurities not listed in the current EU specifications for food additives. Based on their physicochemical properties, the three gases are considered by the Panel to be of low toxicological concern when used as food additives and their dietary exposure very low. The Panel concluded that the use of butane (E 943a), isobutane (E 943b) and propane (E 944) as food additives at the currently permitted uses and use levels does not raise a safety concern. The Panel made some recommendations for amending existing EU specifications for butane (E 943a), isobutane (E 943b) and propane (E 944).